Development of School Environments as Moving Class and Learning Resources for Student Motivation: Pengembangan Lingkungan Sekolah sebagai Moving Class dan Sumber Belajar Terhadap Motivasi Siswa - Novi Amirul Fatah; Ribut Wahyu Eriyanti; Hari Sunaryo (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Learning environments play a crucial role in shaping students’ academic engagement, particularly at the secondary level. The moving class model, which requires students to rotate between subject-specific rooms, offers a dynamic alternative to static classroom settings. Specific background: Many students in junior secondary education experience decreased motivation due to monotonous instructional environments. Knowledge gap: Although moving class has been widely discussed, comprehensive synthesis of its role within school environment development and student motivation remains limited. Aim: This study synthesizes empirical findings on how school environments designed as moving class settings relate to student motivation. Results: The review of 25 empirical studies published between 2020 and 2025 reveals consistent motivational benefits, particularly in intrinsic interest, curiosity, active participation, and achievement orientation. Key contributing factors include flexible learning spaces, diverse resources, technology integration, and teacher-designed interactive activities. Challenges primarily involve time management, coordination among teachers, and infrastructure readiness. Novelty: This review integrates environmental development, learning space design, and moving class practices within a single analytical framework. Implications: Findings support the need for structured planning, collaboration, and facility enhancement to create learning environments that sustain student motivation and meaningful engagement. Highlights • School environment development supports student motivation within moving class settings. • Flexible spaces and varied learning resources foster active student participation. • Effective planning and teacher collaboration strengthen learning environment implementation. Keywords Moving Class, Motivation, High School, Learning Environment, Innovation